Bl. Chavara, an Eminent Visionary Priest of 19th Century of Syro-Malabar Church - Kanjiramattam, Joseph (Asian Horizons, 2009)
In this year dedicated to the renewal of priests I would like to present before the readers an eminent visionary priest of the 19th century of Syro-Malabar Church who laid the foundation of the wonderful growth this Church has achieved now. It is unfortunate that even many leaders of this Church have only a very scanty knowledge about this illustrious son of the Syro-Malabar Church. It is to be admitted also that Chavara’s congregation has not taken sufficient effort to make him known to the public. Chavara’s priestly life and pastoral activities are sources of great inspiration to all priests.